Morfoanatomia de rizomas e raízes de Tillandsia L. (Bromeliaceae) dos Campos Gerais, PR, Brasil - Segecin, Simone; Scatena, Vera Lúcia [UNESP] (Sociedade Botânica do Brasil, 2004)
Morphological and anatomical features of rhizomes and roots were studied in Tillandsia crocata (E. Morren) Baker, T. gardneri Lindl., T. geminiflora Brongn., T. mallemontii Glaziou ex Mez., T. linearis Vell., T. lorentziana Griseb., T. recurvata L., T. stricta Soland. ex Sims., T. streptocarpa Baker, T. tenuifolia L. and Tillandsia sp. They are epiphytes. The rhizomes are horizontal and present intracortical roots. They present uniseriated epidermis or storied cork; cortex with isodiametrical cells, idioblasts with raphide-sacs, and starch grains; uniseriated endodermis presenting thin-walled cells; uniseriated or multiseriated pericycle with thin or thick-walled cells; vascular cylinder presenting collateral vascular bundles. The adventitious roots are intracortical or external. The latter have multiseriated velamen; presenting idioblasts with raphide-sacs, cortical intercellular spaces, exodermis with thick-walled cells; uniseriated endodermis with thin or thick-walled cells; uniseriated pericycle with thin-walled cells; reduced vascular cylinder. The intracortical roots differ of the external ones for the lack of velamen. Most of these adaptative anatomical features might be related to the epiphytic habit of these plants.

Foi estudada a morfoanatomia dos rizomas e das raízes de Tillandsia crocata (E. Morren) Baker, T. gardneri Lindl., T. geminiflora Brongn., T. mallemontii Glaziou ex Mez., T. linearis Vell., T. lorentziana Griseb., T. recurvata L., T. stricta Soland. ex Sims., T. streptocarpa Baker, T. tenuifolia L. e Tillandsia sp., epífitas dos Campos Gerais, Paraná, Brasil. Os rizomas são horizontais, ou levemente inclinados e apresentam raízes intracorticais. São revestidos por epiderme unisseriada ou súber estratificado. O córtex parenquimático é constituído por células isodiamétricas, apresenta idioblastos de ráfides e grãos de amido. A endoderme é unisseriada, com células de paredes finas. O periciclo é uni ou multisseriado, com células de paredes finas ou espessadas. O cilindro vascular apresenta feixes vasculares colaterais. As raízes são adventícias intracorticais ou externas. Estas últimas apresentam velame multisseriado. O córtex apresenta idioblastos de ráfides e grandes espaços intercelulares na região interna. A exoderme apresenta duas a quatro camadas de células com paredes espessadas. A endoderme é unisseriada, com células de paredes finas ou espessadas. O periciclo é unisseriado, com células de paredes finas. O cilindro vascular é reduzido, poliarco. As raízes intracorticais diferem das externas por não apresentarem velame. A presença de rizoma com raízes intracorticais, raízes com velame, espaços intercelulares no córtex interno, idioblastos de ráfides e grande quantidade de células com paredes espessadas são caracteres anatômicos adaptativos, que provavelmente ocorrem como resposta ao hábito epifítico dessas plantas.
Morphology and anatomy of rhizomes and roots in Tillandsia L. (Bromeliaceae) from the Campos Gerais, PR, Brazil
Keywords: Tillandsia; morphology; anatomy; rhizomes; roots; Tillandsia; morfologia; anatomia; rizomas; raízes